PENGARUH RELIGIUSITAS PENGETAHUAN DAN PENDAPATAN TERHADAP MINAT MAHASISWA MUSLIM DALAM MENABUNG PADA BANK SYARIAH - Syuro'ah, Nurul Mubarokatus; Nurafini, Fira (Jurnal Ekonomika dan Bisnis Islam, 2024)
The Islamic financial industry has grown rapidly in recent years, offering services in accordance with Islamic principles that reject usury and speculation while promoting economic justice. The growth of this industry has been influenced by individual interest and decisions to save in Shariah-compliant banks. Students are among the groups with significant potential to drive this growth. This research aims to determine whether religiosity, knowledge, and income affect the interest of Muslim students in saving in Shariah-compliant banks. The research methodology employed is quantitative associative, with religiosity, knowledge, and income as independent variables and savings interest as the dependent variable. Data collection was conducted through a questionnaire distributed to 106 respondents using purposive sampling technique. Data analysis was performed using Multiple Linear Regression. The research findings indicate that religiosity does not have a significant influence on the interest of Muslim students in saving in Shariah-compliant banks. However, knowledge and income positively influence the interest of Muslim students in saving in Shariah-compliant banks. The implications of this research show that Muslim students' decisions in choosing Islamic banks are driven more by rational factors such as knowledge and income, not solely for religious reasons.